Do transaction costs influence smallholder rubber farmers' choice of selling outlets? Evidence from Liberia. Issue 1 (2nd January 2021) - Mulbah, Francis F.B.; Ritho, Cecilia; Mburu, John
ABSTRACT: This article determines the effect of transaction costs and socio-economic factors on smallholder natural rubber farmers' decisions to sell at the farm gate to itinerant traders or in the alternative markets in Liberia. Cross-sectional data were collected from 200 smallholder natural rubber farmers through multistage sampling. The results indicate that transaction costs and socio-economic variables significantly influenced the choice of selling outlets. The study recommends that policy could aim at establishing market support services in the form of market information systems and affordable means of transportation to enhance access to up-to-date market information on trading partners and prices.